Holyoake's Drumbeat Program: Music as a Tool for Social Learning and Improved Educational Outcomes. Issue 1 (22nd July 2009) - Faulkner, Simon; Ivery, Penny; Wood, Lisa; Donovan, Robert
Abstract: This article discusses the development, implementation and impact of a social development program developed by the Holyoake Institute in Western Australia for use in schools. The program DRUMBEAT uses hand drumming to engage young people in social learning that assists them in integrating more fully into mainstream school and community life. DRUMBEAT was developed in response to a range of issues that disadvantaged Indigenous youth experienced within the educational system and acted to reinforce entrenched social exclusion. Operational for five years, DRUMBEAT is currently being delivered in over 350 schools across Australia. Since its inception the program has undergone several evaluations. The most recent of these, and the subject of this report, was conducted by researchers at The University of Western Australia and relates to participants in the program during the 2008 school year. This study demonstrated that participants in the program improved their level of self-confidence, reduced their level of behavioural incidents and reduced their level of school absenteeism.